2007
DOI: 10.1302/0301-620x.89b11.19847
|View full text |Cite
|
Sign up to set email alerts
|

Callus formation during healing of the repaired tendon-bone junction

Abstract: This study was undertaken to elucidate the mechanism of biological repair at the tendon-bone junction in a rat model. The stump of the toe flexor tendon was sutured to a drilled hole in the tibia (tendon suture group, n = 23) to investigate healing of the tendon-bone junction both radiologically and histologically. Radiological and histological findings were compared with those observed in a sham control group where the bone alone was drilled (n = 19). The biomechanical strength of the repaired junction was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Hibino et al recorded radiographically good callus formation at the loaded tendon-bone junction by six weeks [6]. In this study, the callus was observed radiographically at the lower patellar pole by six weeks postoperatively (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Hibino et al recorded radiographically good callus formation at the loaded tendon-bone junction by six weeks [6]. In this study, the callus was observed radiographically at the lower patellar pole by six weeks postoperatively (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…c A radiograph was made at 12 weeks postoperatively; the patella has resumed its normal height and the callus at the tendon-bone junction appears more evident Fig. 4 Lateral view radiograph made 2 years postoperatively shows that the large callus at the lower patellar pole has increased the diagonal length of the patella to provide a false impression of patella baja, but the A/B ratio=0.85 6,16]. On the other hand, mechanical loading too early will only risk a failure of suture threads or permanently lengthen the tendon callus [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations